Konseling dan Promosi Kesehatan untuk Pencegahan Hipertensi bagi Masyarakat Dukuh Bintaran, Bantul, DIY - Sulistyawati Sulistyawati (Jurnal Pengabdian Pada Masyarakat, 2019)
HEALTH COUNSELING AND PROMOTION IN THE PREVENTION OF HYPERTENSION FOR THE COMMUNITY OF BINTARAN HAMLET, BANTUL, DIY. Hypertension is a condition of increased blood pressure in arteries that increase the cause of the heart to work more than usual to circulate blood through the blood vessels. Precautions if not properly treated will cause other diseases such as sroke. This dedication is carried out with active lectures and discussions with participants. From these activities it is known that people already know the hypertension and the way of prevention but difficult to realize in everyday life. So, in the future there should be a creative health promotion effort and target the right people/groups that can bring about change.